IMPLEMENTASI MULTIMEDIA INTERAKTIF WEBSITE GENIALLY PADA PEMBELAJARAN IPAS SEKOLAH DASAR: KAJIAN LITERATUR - Oktafiastuti; Nuni Widiarti; Decky Avrilianda (Universitas Negeri Semarang, 2026)
Research on website-based interactive multimedia has grown significantly alongside the increasing demand for digital learning in elementary education, including the use of Genially as an innovative platform supporting interactive instruction. This study aims to analyze the characteristics and implementation of Genially-based interactive multimedia, examine its pedagogical impact on students’ motivation, engagement, and learning outcomes, and map research trends and future directions in elementary school learning. The study employed a Systematic Literature Review (SLR) method using Google Scholar data sources through Publish or Perish within the 2022–2026 publication period. From an initial 100 articles, a rigorous screening process resulted in 20 relevant articles for thematic analysis. The findings indicate that Genially possesses key characteristics such as interactive visuals, web-based flexibility, and multimedia integration, making it highly feasible for instructional use. Furthermore, Genially consistently improves students’ motivation, engagement, and academic achievement. Research trends also reveal a shift from media validation studies toward broader pedagogical impact evaluation. This study contributes to strengthening the conceptual foundation for developing Genially-based interactive multimedia and provides future research directions for more contextualized innovation in elementary education.